Frases en euskera desconocidas en una comedia impresa en 1550 - Ibisate, Ángel (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2001)
In the following article, after an introduction about texts in the Basque language which can be found in works in other languages, the author refers to some short sentences in Basque that he has found in a comedy in Spanish printed in 1550. In the article there are some facts about the author and the work, referring particularly to the bibliographic aspects of the work, and finally there is the transcription of the sentences in the Basque language and their nearest context.